MODEL PEWARISAN KEPEMIMPINAN DZURRIYYAH DI PESANTREN SITUBONDO DAN PROBOLINGGO - Mahfudz Sidiq (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
Substantive findings show: First, the model of leadership inheritance of each dzurriyyah; charismatic, managerial, and transcendent-transformative, by: a) introducing their regeneration to the guest who visitingIslamic boarding school, b) oblige potential alumni settled in Islamic boarding school environment, c) developing managerial leadership model,d) determining regulation and policy of Islamic boarding school through transcendent approach. For maintain the sustainability of two Islamic boarding school, the leadership model used byKiai is keeps the dzurriyyah line, with priority; a) sons, b) dzurriyyah directly, c) the nearest immediate offspring, and d) the nearest indirect offspring. Second, the inheritance model in maintain the quality of knowledge of kiai, based on the principles including: a) maintainingthe continuity of teacherswith their predecessors, b) maintaining the continuity of place where the study of his predecessors, c) building, perfecting, and developing Islamic boarding school institution. Third, the networking model in Islamic boarding schoolinstitution by several ways involve:a) build strategic places such as hotels in Makkah, restaurants, establish relationships with various state ministries, and maintain the heritage of Islamic boarding school, b) build a place for community service and empowerment such as gas stations, fishing boats, a mediator of tobacco farmers with PT Gudang Garam, and establish relationships with Islamic boarding school’s givers.